INVESTIGATION OF SURFACE PLASMON RESONANCE ACETONE VAPOUR BIOSENSOR FOR NON-INVASIVE SCREENING AND MONITORING OF DIABETES - USMAN, FAHAD (2021)
Diabetes is a disease that causes complications to human organs. It is currently diagnosed invasively using blood glucose test. Fortunately, non-invasive diagnosis can be achieved through detection of acetone vapour due to its correlation with blood glucose where >1.8 ppm indicates diabetes. The widely investigated acetone vapour sensors based on metal oxide semiconductor (MOS) features high operational temperature, instability and cross-sensitivity. This work presents a non-invasive way of detecting acetone vapour using surface plasmon resonance (SPR) technique at room temperature. In order to evaluate the best acetone sensitive layer, p-toluene sulfonic acid doped polyaniline (PANI), PANI-chitosan composite, PANI-`reduced graphene oxide (RGO) composite, chitosan-polyethylene glycol (chitosan-PEG) and a ternary composite (comprising of PANI, reduced graphene oxide (RGO) and chitosan were synthesized and characterized using FTIR, UV-Vis, XPS, FESEM and AFM.